Newspaper portrayal of mental illness in England, Canada, Portugal, Spain and Japan = Representación de las enfermedades mentales en periódicos de Inglaterra, Canadá, Portugal, España y Japón - Vengut Climent, Empar (Revista Española de Comunicación en Salud, 2018)
Abstract: Research concerning media portrayals of mental illnesses and the effects such portrayals might have on the public has usually been carried out within one country as a geographical limit. Herein, we analyse the results of the research carried out through the analysis of newspapers in 5 different disperse countries around the world in the last decade; England, Canada, Portugal, Spain and Japan. Some of these countries have started national campaigns to reduce the stigmatisation of these conditions, including a focused awareness on Mental Health communication in media. Despite the heterogenicity of the societies studied and the different measures adopted, there is still a negative portrayal of mental illnesses in newspapers, which contributes to the ongoing mental illness stigmatisation. Other media also showed similar results. Moreover, this review intends to give a general vision on how research in this area is carried out and propose a reflection on how it should be pursued. Keywords: media; newspaper; stigma; western countries; mental health. Resumen: La investigación relacionada con la imagen que los medios de comunicación proporcionan de las enfermedades mentales y los efectos que esta imagen tiene en el público se suelen realizar dentro de un país como frontera geográfica. En esta revisión se analizan los resultados obtenidos en diferentes estudios que analizan la cobertura de la salud mental en periódicos de 5 países diferentes, Inglaterra, Canadá, Portugal, España y Japón. Algunos de estos países han lanzado campañas a nivel nacional para reducir el estigma relacionado con estas enfermedades y presentan una parte focalizada en la comunicación de la salud mental por parte de los medios de comunicación. A pesar de la diversidad de las sociedades estudiadas y de las diferentes medidas tomadas en cada uno de estos países, sigue habiendo una representación negativa de las enfermedades mentales en los periódicos, lo que contribuye a la perpetuación del estigma. Además, se han obtenido resultados semejantes en otros medios. Finalmente, esta revisión intenta dar una perspectiva general de cómo se llevan a cabo este tipo de investigaciones y propone una reflexión de cómo debería de ser. Palabras clave: medios de comunicación; periódicos; salud mental; estigma; enfermedad mental.